Evaluation of Added Sodium and Chloride for 15 to 24 lb Nursery Pigs - D. Shawk; M. Moniz; A. B. Clark; R. D. Goodband; J. C. Woodworth; M. D. Tokach; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 360 pigs (Line 241 × 600; DNA, Columbus, NE) were used in a 14-d growth trial to determine if the response to added dietary salt in nursery pigs (15 to 24 lb) was due to either the Na or Cl concentration in the diet. Upon entry to the nursery, pigs were allotted by BW and fed a common starter diet (0.33% Na and 0.76% Cl) for 7 d after weaning. On d 7 after weaning, considered d 0 in the trial, pens were assigned to 1 of 4 dietary treatments that were fed from d 0 to 14. The 4 experimental treatments included a 10% dried whey diet with 12 lb/ton added salt (0.37% Na and 0.75% Cl); or 3 diets with dried whey replaced by 7.2% lactose containing either: 7 lb/ton added salt (0.18% Na and 0.47% Cl); 15.5 lb/ton added salt (0.35% Na and 0.72% Cl); or 23 lb/ ton sodium bicarbonate and 8 lb/ton potassium chloride (0.35% Na and 0.45% Cl), respectively. From d 0 to 14, pigs fed the 10% dried whey diet with 12 lb/ton added salt or the diet with lactose and 15.5 lb/ton added salt had improved (P<0.05) ADG compared to pigs fed the lactose diet with 7 lb/ton added salt, with pigs fed the lactose diet with 23 lb/ton sodium bicarbonate and 8 lb/ton potassium chloride intermediate. Pigs fed the 10% dried whey diet with 12 lb/ton added salt had greater (P<0.05) ADFI than those fed the lactose diet with 7 lb/ton added salt, with pigs fed the lactose diet with 15.5 lb/ton added salt and the lactose diet with 23 lb/ton sodium bicarbonate and 8 lb/ton potassium chloride intermediate. However, F/G tended to be poorest for pigs fed 10% dried whey compared with pigs fed 7.2% lactose and 15.5 lb/ton added salt, with others intermediate. In conclusion, diets should be formulated with enough added salt in order to meet NRC (2012) recommendation of dietary Na concentration of 0.35%, which is higher in Na than many nursery diets for 15 to 25 lb pigs.
Keywords: chlorine (Cl); sodium (Na); nursery pig; salt